Materialval i VA-system baserat på miljöoch klimataspekter samt anläggning-, driftoch underhållskostnader - Carlsson, John; Vainio, Axel (My University, 2024)
This thesis was commissioned by Växjö Kommun and aims to investigate the three sustainability dimensions in relation to different materials and their role in the water and sewage industry. Växjö Kommun seeks more data to support their material selection decisions in projects, as current decisions are sometimes based on personal opinions. The materials explored include PE and ductile iron in pressure pipelines, PP, PVC, and concrete in gravity pipelines, and PP and concrete in two types of wells. The ecological sustainability dimension has been analyzed through quantitative calculations based on EPD studies and LCA conducted for the various products, as well as discussions on environmental perspectives with municipalities. Since not all aspects are included in the product environmental declarations, the analysis only covers the production stage, with values for the materials also sourced from Granta EduPack. The economic sustainability dimension has been investigated by analyzing damage history and consulting with knowledgeable individuals from Gothenburg, Kalmar and Växjö who work with damage frequency, damage history, and costs related to these damages. The social sustainability dimension has been examined through interviews with individuals from three different municipalities, focusing primarily on differences in working conditions when using different materials. The results show that there are ecological differences between materials but that it should be further explored as only a small part of the entire life cycle has been able to be analyzed for all products, EPD-studies were also missing for certain well-components and other products that would have been relevant to compare. The interviews reveal that some municipalities currently do not consider environmental aspects when selecting materials for piping. From an economic perspective, more resources are required to accurately determine all cost differences throughout the products' life cycles. Regarding working conditions and other social aspects, there should be no significant differences if the work is carried out correctly, even though the work processes may vary depending on the material chosen.
Keywords: pipe; well; EPD; PE; PP; PVC; ductile iron; concrete